The analysis of ion-transporting ATP-ase activities in human blood erythrocytes under the influence of inflammation in tonsils - Nurishchenko, N. Ye.; Andreychenko, S. V.; Miroshnichenko, N. S. (Biophysical Bulletin, 2018)
The activities of K, Na-ATPase, Mg-ATPase and Ca-ATPase in human blood erythrocytes have been studied. Under the aggravation of inflammation process in tonsils total-ATPase activity started diminishing significantly, reached the minimum value during quinsy and then began gradually restoring its activity in the rehabillitation period. At the compensatory phase of recurrent tonsillitis ion-ATPases showed vivid flash in enzyme activities thereby triggering the normalization of transmembrane potential and stabilization of electrical charge on the erythrocyte surface as well.